Utilização de zeólita NH4 -Y como adsorvente de bário em água produzida : estudo cinético e termodinâmico - Barbosa, Cintya D´angeles do Espirito Santo (2011)
In the last decades, with progress of the researches and of the knowledge in the area of aqueous effluent treatment, the adsorption became used as an important unitary operation, coming as an alternative important and economically viable in many cases. Before the exposed, the main objective of this work is to study the potential use of the NH4Y zeolite as adsorbent of originating from barium the produced water, through a kinetic and thermodynamic study. The obtained results evidenced that the produced water of the fields of Siririzinho/SE onshore, it is saline and it contains high concentrations of the ions: potassium, sodium, calcium, magnesium, and sulfate. The pH was close of the neutrality. It was also observed to the presence of the cations barium and strontium in concentrations reasonably high. In a general way, it was observed in the infrared spectra of the incrustation samples, bands compatible with the presence of a mixture of oil residues and of mineral components. The X-ray diffractograms patterns of incrustation samples suggest the presence of montmorillonite, quartz, calcite and barite. In the infrared spectra of NH4Y zeolite, the most predominant bands happened in the range of 1250 to 950 cm-1 and 790 to 650 cm-1, indicating asymmetrical stretching mode (←OTO←) and symmetrical stretching mode (←OTO←), respectively. Through the diffraction patterns of the NH4Y zeolite can observe that the sample consists of material with a faujasite-type structure with high purity. Thermogravimetric curve of NH4Y zeolite presented three main stages of decomposition, and the percentage of residual material zeolite was 72.5%. The obtained curve from the experiment for determining the pH of zero point of charge (pHPCZ) showed that the experimental pHPCZ was 6.07. To study the mass effect on barium adsorption by NH4Y zeolite was observed that the percentage removal increases significantly with increasing mass. Through the results of ion competition, we can see that the presence of other ions (different of barium) in produced water considerably affects its adsorption capacity. The kinetic curves showed that the adsorption capacity increases with contact time and these values were higher with increasing initial concentration. Kinetic models used in this work through the methodologies linear and nonlinear can be noted that the kinetic data best fit to the exponential kinetic model of Avrami. It was observed that the intraparticle diffusion is not the determining factor in the barium adsorption process by NH4Y zeolite. Among the equilibrium isotherms tested the data was best fitted to Sips. The thermodynamic parameters of barium adsorption by zeolite NH4Y calculated by the indirect method of van't Hoff and isosteric data, showed that the process is favored for higher temperatures. We obtained negative values of ΔG indicating that the interactions are spontaneous, entropy values of adsorption (ΔS) tendency to positive values with increasing temperature obtained by the van't Hoff equation, and positive for those obtained by isosteric data, indicating that the process tends to greater disorganization, and finally values of enthalpy ΔH tendency towards positive values with increasing temperature by the van't Hoff equation, and positive for the isosteric data, indicating that in general the barium adsorption by NH4Y zeolite is an endothermic process in nature. Initial tests using real water samples produced showed that the adsorption of barium effluent is less real than those realized in synthetic systems. The adsorption tests were presented as promising for the application of zeolite NH4Y in the oil industry as a secondary method for the treatment of produced water.